The Effect of Context on Voice Onset Time - Ziyad Rakan Kasim (PROSPECTIVE RESEARCHES, 2023)
Voice onset time (VOT) is reduced when English /p,t,k/ are preceded by initial /s/ before a vowel, which results in a loss of the aspiration of /p,t,k/. The present paper attempts to test this phenomenon in Mosuli Arabic. The three voiceless stops /p,t,k/ are examined in two contexts: initially and when preceded by /s/. Words containing these stops were recorded and analyzed spectrographically and the VOT was measured for each stop initially and when preceded by /s/. The results of the study show that the VOT values of the voiceless stops do not show the difference noted in English; the context did not have a statistically significant effect on the VOT values.